Challenges and pitfalls in risk management - an executive's perspective - Schrøder, Peter Winther (Henry Stewart Talks, 2012)
Examples of risk management malpractice, What is the aim of managing the various types of risk, Flaws in current risk management practice, Integration of the risk management and strategic planning process, Broaden risk management to a wider part of the organization, Coping with intangible, complex and difficult to manage risk, Various aspects of operational risk, How to achieve a better understanding of the operational risk landscape, Loss register, Root cause analysis, Risk control self-assessment, Categorizing operational risk, Scenario analysis, Blind spots, Prerequisite for successful identification and mitigation of operational risk, How to manage business risk, How to engage various stakeholders in discussions related to more traditional and foreseeable business risk, Dealing with black swans, Eliminate biases, Integrate black swans into the strategic planning process